PENGGUNAAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PUISI - Sukaharsilawati, Made Ayu (LP2M IKIP PGRI Bali, 2018)
This research has an objective to improve the teaching of Indonesian language and literature, and to improve students' poetry reading skill of class XII AP 2 SMK Nusa Dua Badung in lesson 2014/2015 through contextual approach (CTL). The results of this study is the ability of students of class XII AP 2 SMK Nusa Dua Badung in reading poetry is very good. It is evident from the average value obtained by students have increased from each cycle. In cycle I the average of students is 70.71%. In cycle II the average score of students' poetry reading ability increased to 82.28%.